Atapuerca Neanderthal landscape at Fuente Mudarra site in Burgos, Spain, during Marine Isotope Stages 5–3. Issue 1 (January 2021) - Santamaría, Marta; Navazo, Marta; Benito-Calvo, Alfonso; Alonso, Rodrigo; López, Gloria I.; Carbonell, Eudald
Abstract: Fuente Mudarra is on a gentle slope on the left bank of the Pico River, near Sierra de Atapuerca, Burgos, Spain. A 12−m 2 test pit was dug at this large open-air site between 2012 and 2017. Several upper Pleistocene archaeological levels were documented. Results from Fuente Mudarra confirm that Neanderthal groups, little represented at cave sites, occupied Sierra de Atapuerca from the end of the middle Pleistocene and during the upper Pleistocene. The site also provides insight into Neanderthal spatial organization in the Atapuerca area and whether they used the caves in an occasional, non-habitual way like the open-air sites.